Analysis on the impact of investments, energy use and domestic material consumption in changing the Romanian economic paradigm - Popescu, Gheorghe H.; Andrei, Jean Vasile; Nica, Elvira; Mieilă, Mihai; Panait, Mirela (Technological and Economic Development of Economy, 2019)
The main aim of the paper is to assess the impact of fix capital, energy use and domestic material consumption in changing the inland Romanian economic paradigm, from an economic perspective, using the intensive form of the Cobb-Douglas function. In order to identify various connections of economic growth, sustainable development, energy usage has determined the application of the vector error correction (VEC) model and the implied error correction term (ECT). This method was chosen based on the premise that it has a high degree of applicability and it can be used in order to revile significant aspects terms of indicator significance and displays. The results obtained during the research confirm that both in Romania and at EU-28 level there are determinant and significant elements shaping a proactive economic policy.